P509 Surgery and biologic prescription rates for Crohn's disease in Lothian, Scotland; an updated population-based cohort study. (30th January 2023) - Jenkinson, P; Plevris, N; Lyons, M; Gros Alcalde, B; Derikx, L; Constantine-Cooke, N; Arnott, I; Jones, G; Lees, C
Abstract: Background: Recent years have seen a shift in Crohn's disease (CD) management to earlier initiation of biologic therapy using a treat to target strategy. We have previously published a population based cohort showing a reduction in CD surgery rates and increase in biologic prescribing over time. Methods: The aim of this study was to identify trends in rates of surgery and biologic prescription in CD over time in a population-based cohort. All incident CD cases diagnosed between 01/01/2000 and 31/12/2017 were identified from the Lothian IBD registry . Abdominal surgeries and biologic prescription from diagnosis to July 31st 2022 were identified from national coding data and the EHR.. The cohort was divided into quartiles by date of diagnosis: 2000-04, 2005-08, 2009-13 and 2014-17; comparison was performed using the log rank test. Results: 560/1753 (30.3%) incident CD cases underwent resectional surgery over a median of 12 years follow-up (IQR 8-14). The overall cumulative incidence rates of first surgery at 1, 5, and 10 years were 7.41% (95% CI, 3.4%–10.4%), 16.1% (12.2%-19.6%), and 29.9% (25.2%–34.4%), respectively. When comparing temporal trends there was a significant reduction in surgical rates by date of diagnosis (logrank p <0.00) (Fig 1). There was no difference in the rate of repeat surgery between cohorts (p=0.156). Fig 1. Kaplan–Meier curves for risk of first surgery in Crohn's disease during follow-up of cohorts defined by year of diagnosis. A total of 703/1753 patients (34.3%) were prescribed biologics. The rates of first biologic prescription at 1, 5, and 10 years were 8.2% (CI:, 4.4%– 12.3%), 22.2% (18.8%-25.6%), and 34.7% (31.4%–37.8%) respectively. When comparing temporal trends, there was a significant increase in biologic prescription rates by date of diagnosis (logrank p <0.001; Figure 2). Biologic prescription in the first year after diagnosis rose significantly over time from 1.0% in the earliest cohort to 22.2% in the latest. Fig 2. Kaplan–Meier curves for risk of first biologic in Crohn's disease during follow-up of cohorts defined by year of diagnosis. Conclusion: We have identified a significant increase in the cumulative incidence of biologic prescription and use of biologics earlier in the patients IBD journey over time. This has been parallelled by a significant reduction in the incidence of first surgery which has been maintained with longer follow up.